Cho hàm số (f( x ) = ln frac((x + 1))((x + 4))). Tính giá trị biểu thức (P = f'( 0 ) + f'( 3 ) + f'( 6 ) + ... + f'( (2019) )).

Lưu lại

Cho hàm số $f\left( x \right) = \ln \frac{{x + 1}}{{x + 4}}$. Tính giá trị biểu thức $P = f'\left( 0 \right) + f'\left( 3 \right) + f'\left( 6 \right) + ... + f'\left( {2019} \right)$. 

Đáp án: C

Ta có $f(x)= \ln \dfrac{{x + 1}}{{x + 4}}$$ \Rightarrow f'\left( x \right) = \dfrac{{{{\left( {\dfrac{{x + 1}}{{x + 4}}} \right)}'}}}{{\dfrac{{x + 1}}{{x + 4}}}} = \dfrac{\dfrac{3}{{{{\left( x + 4 \right)}^2}}}}{\dfrac{x + 1}{x + 4}}$

$ \Rightarrow f'\left( x \right) = \dfrac{3}{{\left( {x + 1} \right)\left( {x + 4} \right)}}$

$ \Rightarrow f'\left( x \right) = \dfrac{{\left( {x + 4} \right) - \left( {x + 1} \right)}}{{\left( {x + 1} \right)\left( {x + 4} \right)}} = \dfrac{1}{{x + 1}} - \dfrac{1}{{x + 4}}$

Khi đó $P = f'\left( 0 \right) + f'\left( 3 \right) + f'\left( 6 \right) + ... + f'\left( {2019} \right)$

$\begin{array}{l} \Rightarrow P = 1 - \dfrac{1}{4} + \dfrac{1}{4} - \dfrac{1}{7} + \dfrac{1}{7} - \dfrac{1}{{10}} + ... + \dfrac{1}{{2020}} - \dfrac{1}{{2023}}\\ \Leftrightarrow P = 1 - \dfrac{1}{{2023}} = \dfrac{{2022}}{{2023}}\end{array}$

Chọn C.

TOP THÀNH VIÊN NỔI BẬT

    Xem top 100 thành viên